Positive Self-Talk: an Unexploited Self-Management Cognitive-Motivational Strategy at the University Level and Its Effect on Students’ Oral Performances. - BOULKRAA, Meriem (Journal of Human Sciences, 2016)
Positive self-talk iscurrently considered one of the most potent self-management learning strategies and as a major factor within educational psychology that can fully be exploited by college students in order to improve their academic performance, in general, and their oral performance, in particular. The present study is an attempt towards sensitizing learners on the significance and the usefulness of positive self-talkin aiding them produce more natural proficient English conversations . It also attempts to demonstrate that such a type of self-management learning strategy has generally been found to be effective in enhancing students’ performance in a variety of skills (as the conversational skill), by emphasizing the link between what students say to themselves; either positive or negative self-messages, and how they perform orally. The paper first provides a theoretical background about the concept of self-talk. Then, it displays how positive self-talk has a vital importance for students, through the analysis of a questionnaire carried out on a sample of first-year ENSC students. Results reveal that positive self-talk as a cognitive-motivational method is, to a great extent, efficacious and successful in bolstering up students’ oral performance/achievement.